Finding Topic Experts in the Twitter dataset using LDA Algorithm - Shirolkar, Ashwini Anandrao; Deshmukh, R. J (International Journal of Computer Sciences and Engineering, 2025)
Expert finding which aims to identifying people with the relevant expertise or practices on a given topic query. In blogging services like Twitter, the expert analysis problem has gained big attention in social media. Twitter is a new type of media giving a publicly available way for users to publish 140-character short messages (i.e., tweets). However, earlier systems cannot be directly applied to twitter expert finding difficulty. They generally rely on the supposition that all the documents linked with the candidate experts receive implicit knowledge related to the expertise of individuals. Whereas it might not be directly allied with their expertise, i.e., who is not an expert, but may publish/re-tweet a substantial amount of tweets including the topic words. Recently, several attempts use the relations among users and twitter list for expert finding. Nevertheless, these strategies only partly utilize such relationships. To address these issues generate a probabilistic method to jointly exploit three types of relations (i.e., follower relation, user-list relation and list-list relation) for finding experts. LDA algorithm is applied to finding topic experts. LDA is based upon the concept of searching for a linear combination of variables (predictors) that best separates two classes (targets). Semi-supervised Graph-based Ranking approach (SSGR) to offline measure the global authority of users. Then, online compute the local relevance between users and the given query. Then order all of the users & find top-N users with the highest ranking scores. Therefore, the proposed method can jointly exploit the different types of relations among users and lists for improving the precision of finding experts on a given topic on Twitter.